Implementation of TPACK-Integrated Problem-Based Learning to Improve Students' Higher-Order Thinking Skills on Newton's Laws - Meltinur Asqory; Fibrika Rahmat Basuki; Dedi Sastradika (Journal La Edusci, 2026)
The low Higher Order Thinking Skills of Indonesian students in Physics lessons encouraged the conduct of this quasi experimental research to investigate the influence of the problem based learning model integrated with technological pedagogical content knowledge on newton's law material. Involving 65 MAN 1 Jambi City students divided into three groups, the results of the kruskal wallis test showed a significant difference (p=0.000) with the technological pedagogical content knowledge integrated problem based learning experimental group achieving the highest average score (90.45) compared to the problem based learning group alone (81.36) and control (75.91). The integration of technologies such as PhET simulation and google sites has been proven to be significantly more effective in improving students' evaluation and creation skills. This study concludes that the combination of problem-based pedagogy with technological proficiency is the main key in transforming learning from memorization into critical and creative self discovery to face the digital era.